Salam and Parallel Salam Operations (Sharia Requirements and Accounting Treatments) - Dr. Ali Muftah Ghaith Al-Zawali; Dr. Ibrahim Muhammad Ahmeida; Prof. Dr. Hisham Kamel Qashout (Journal of Scientific and Human Dimensions, 2026)
This study focused on explaining the important aspects related to the Salam contract, as it is among the sales contracts used recently in Islamic banking. This is because it provides a financing formula that is flexible and responsive to the needs of different customers, whether short-term, medium, or long-term financing, and also provides the needs of multiple segments of customers, whether they are agricultural or industrial producers, contractors, or merchants, as well as its response to financing operating expenses and expenses. Other capitalism. The study also demonstrated the possibility of practical application of Accounting Standard No. (7) issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), with all its legal and technical requirements. The most important results of this study are: 1) Salam and Parallel Salam are characterized by characteristics that make them a financing alternative in Islamic banking. 2) The existence of an integrated scientific framework for the contract of Salam and Parallel Salam that can be precisely defined. Accordingly, the study recommended the following: 1) The necessity of activating the legal and accounting standards issued by the authorities responsible for Islamic finance, and knowing their compatibility with practical practices. 2) Taking into account the specificity of banking legislation and law issued in Libya when dealing with Islamic financial products, including Salam and Parallel Salam. 3) Requesting educational and training institutions to introduce knowledge related to Islamic finance in its various branches.